METAPHORICAL FRAMING OF CLIMATE CHANGE IN ENGLISH NEWS DISCOURSE - Sophie Mueller (International Journal of Literature and Language Studies, 2026)
This article investigates metaphorical framing of climate change in English news discourse within the broader field of linguistics and applied language studies. The study uses a specialised corpus of 95 recent English-language news reports and editorials on climate policy and applies corpus-assisted metaphor identification followed by semantic grouping of source domains. The main finding is that war, journey, disease, and market metaphors were used to frame urgency, responsibility, risk, and political choice. The article argues that metaphor analysis reveals how news language guides public understanding of environmental action. The discussion is relevant to researchers, teachers, curriculum designers, and graduate students who need concise but systematic models of linguistic inquiry.